2015
DOI: 10.1097/pas.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Polypoid Adenomyoma of the Uterus

Abstract: Atypical polypoid adenomyoma (APA) is an uncommon uterine lesion that commonly recurs after local excision and is occasionally associated with or precedes the development of atypical hyperplasia or endometrioid adenocarcinoma. Despite the fact that about 230 cases have been reported in the literature, only 2 studies of 6 and of 7 cases have investigated the molecular aspects; as such, molecular alterations that occur in APA remain largely unknown. We undertook a comprehensive immunohistochemical and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 47 publications
0
14
1
1
Order By: Relevance
“…Previous small-scale studies have shown that APAM is associated with MLH1 hypermethylation, and microdissected glandular components were shown to contain CTNNB1 mutations (31,32). In addition, KRAS mutation was found in 4/16 cases (25%) without BRAF mutation (33), in contrast with the absence of RAS mutations in our APAM samples (0/12). Larger studies employing laser-microdissection followed by RAS mutation analysis in individual APAM components, will be necessary to draw final conclusions on this issue.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous small-scale studies have shown that APAM is associated with MLH1 hypermethylation, and microdissected glandular components were shown to contain CTNNB1 mutations (31,32). In addition, KRAS mutation was found in 4/16 cases (25%) without BRAF mutation (33), in contrast with the absence of RAS mutations in our APAM samples (0/12). Larger studies employing laser-microdissection followed by RAS mutation analysis in individual APAM components, will be necessary to draw final conclusions on this issue.…”
Section: Discussioncontrasting
confidence: 59%
“…Das Stroma ist immunhistochemisch positiv für SMA, aber negativ für Desmin und Caldesmon, wodurch der Name Adenomyofibrom besser passen würde [35]. Der häufige Verlust von PTEN und häufige andere molekulare Veränderungen wie Mikrosatelliteninstabilität und KRAS-Mutationen legen die neoplastische Natur und die Verwandtschaft mit der atypischen Endometriumhyperplasie nahe [36]. Ein myoinvasives Wachstum fehlt.…”
Section: Gemischte Epitheliale Und Mesenchymale Tumorenunclassified
“…APA is a biphasic lesion that is composed of atypical endometrial glands and fibromuscular stroma. Because the glandular component shows endometrioid features with irregular architecture and cytologic atypia, pathologists sometimes have difficulties in differentiating APA from myoinvasive adenocarcinoma 3 . This distinction is crucial and influences the clinical management of patients, allowing fertility preservation for patients with APA 1-6 .…”
Section: Introductionmentioning
confidence: 99%
“…To discriminate between these cases, some immunoistochemical markers are needed. Previous studies investigated the expression of muscular and endometrial stromal markers in APA 3 , 7-12 .…”
Section: Introductionmentioning
confidence: 99%